Análises das propriedades ópticas, morfológicas e estruturais de pontos quânticos de PbS sintetizados a partir de diferentes concentrações de dopantes - Paula, Priscila Marques Naves de (2006)
PbS quantum dots has been grown in oxide glasses by two distinct methodologies according to the dopants, using the fusing method at 1200ºC. The host glass matrices used were SNAB (SiO2.Na2CO3.Al2O3.B2O3) and SNABP (SiO2.Na2CO3.Al2O3.B2O3.PbO2), with PbS bulk and S (sulphur) added as dopants, respectively. Thermal treatments were applied in a systematic way in order to allow a controlled growth of quantum dots. Different experimental techniques were realized in order to study the growth kinetic of dots as a function of thermal treatment times and dopant concentrations. It was analyzed thermal properties of the glass matrices by Calorimetry Scanning Diferencial (DSC). Many techniques have allowed discussion of the optical properties by Optical Absorption (OA) and Photoluminescence (PL), morphologic properties by Atomic Force Microscopy (AFM), and structural properties by X-Ray Diffractometry (DRX) of the nanocrystals. Qualitative and quantitative analyse of the chemical composition of the samples has been possible by spectrometry of Fluorescence of Raios-X (FRX). Using the ] 4 4 [ . × p k r r method we were able to estimate the avarage diameter of the PbS quantum dots. Calculations of dispersion sizes of PbS quantum dots, from the AO bands, has been presented. We have found the dependence between the quantum dot gap and the dopant concentrations. The relation between the Stokes Shift and the average size of the PbS quantum dots was also presented. Through the previous results, we have defined the methodology referring the host glass matrix SNABP with S bulk added as the most favorable to the growth PbS quantum dots with low size dispersion.